Analisis Perbedaan Item Pekerjaan dan Volume Dengan Realisasi Lapangan di Pembangunan Lanjutan Gedung Kejari Tapaktuan - Muhaida Sapitri; Meylis Safriani (Publikasi Indonesia, 2023)
Work Items and Volume are one part of construction management. Project Management is the process of implementing management functions (planning, implementing, controlling and coordinating) in a project by using existing resources effectively and efficiently in order to optimally achieve project objectives. Analysis of Construction Management in the Continuation Development Project for the Tapaktuan District Attorney's Special Crime Building (Kejari) in South Aceh District includes Work Items and Volumes. The final results obtained from the analysis of work items and volume in the Continuing Development Project of the Tapaktuan Kejari Building in South Aceh Regency after planning using a network diagram takes 150 (one hundred and fifty) / working days for the construction of the overall structure of the building is compatibility with work in the field with funding sources APBK T.A. 2022 with a budget ceiling of IDR 650,000,000 and an HPS value of IDR. 649,995,240.43.